Nightshade - Kendig, Ronie (Kendig, Ronie. Discarded heroes, 2010)
"After a tour of duty in a war-torn country, embattled former Navy SEAL Max Jacobs finds himself discarded and alienated from those he loves as he struggles with war-related PTSD. His wife, Sydney, files a restraining order against him and a petition for divorce. Max is devastated. Then a mysterious man appears. He says he's organizing a group that recycles veterans like Max. It's a black-ops group known as Nightshade. With the chance to find purpose in life once again, Max is unable to resist the call of duty and signs on. The team handles everything with precision and lethal skill--until they're called upon to rescue a missionary family froma rebel-infested jungle and avoid a reporter hunting their identities. Will Max yield his anger and pride to a force greater than him--love?"--P. [4] of cover.